Menuju Pendidikan Agama Kristen yang Relevan: Teroka Teologis Peran Teknologi Informasi dalam Menghadapi Tantangan Abad Ketiga - Sampe, Naomi; Sanderan, Rannu; Hendra, Fery; Kelana, Fajar (Institut Agama Kristen Negeri Toraja, 2023)
Abstract: This research aims to explore the role of Information Technology (IT) in the development of Christian Religious Education. The third millennium, also known as the information age, is characterized by cyber technology and uncertainty. The millennial generation lives in a borderless world where information is readily available in real time. The theoretical paradigm applied in this context is that it is important to invite and motivate scientists from various fields to align their faith with their job specifications in the context of Christian education. Ultimately, this research concludes that educators must utilize IT and communication technologies to develop Christian education and strengthen the faith of God's people. This article explores the role of IT in developing Christian education in the context of the current age. It argues that the use of IT and communication technologies is essential in meeting the challenges of the current era and in fulfilling the mission of Christian education. From a theological perspective, the primary objective of our service in Christian religious education is solely for the glory of God.